Preliminary Studies on the Development and Evaluation of Instant Pounded Yam from Dioscorea alata - Abiodun A Adeola; Bolanle O Otegbayo; Sola Ogunnoiki (Journal of Applied Sciences and Environmental Management)
Of all the species of Dioscorea, D. alata possesses higher multiplication ratio and better storability, and requires less capital and labour to produce than the most common specie, D. rotundata. Exploitation of the industrial potential of D. alata by diversifying its utilisation through the development of novel products will expand its utilisation. This study therefore investigated the potential of developing instant poundo yam flour from D. alata. Instant poundo yam flour was prepared from D. alata by peeling, dicing and immersing yam tubers in sodium metabisulphite solution (800 ppm for 20 min). The tubers were thereafter blanched at 70 oC for either 5 or 10 min, dried in a cabinet dryer at 60 oC for 72 hr, milled and sieved (600 μm) to obtain two experimental samples of poundo yam flours. The proximate composition of the flours was determined using standard methods. Sensory evaluation was conducted to determine the sensory attributes [colour, flavour, taste, textural quality (strecthability, adhesiveness, cohesiveness, smoothness) and general acceptability] of the flours. The two instant poundo yam samples were further compared with a commercial poundo yam in terms of the sensory attributes. There was no significant difference (p≤ 0.05) in the proximate composition of the two experimental instant poundo yam samples but their textural quality differed significantly (p ≤ 0.05). Instant poundo yam blanched for 10 min recorded higher sensory scores than the one blanched for 5 min and compared fairly well with the reference sample. An acceptable instant poundo yam has been developed from D. alata.